2019
DOI: 10.1111/acps.13098
|View full text |Cite
|
Sign up to set email alerts
|

Fathers’ alcohol use and suicidal behaviour in offspring during youth and young adulthood

Abstract: Fathers' alcohol use and suicidal behaviour in offspring during youth and young adulthood Landberg J, Danielsson A-K, Hemmingsson T. Fathers' alcohol use and suicidal behaviour in offspring during youth and young adulthood.Objective: To examine the association between various indicators of father's alcohol use and suicidal behaviour in offspring during youth and young adulthood. Methods: The study is based on a cohort of 68 910 Swedish citizens who were born between 1970 and 1985 and have fathers who participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…It is not surprising that drug use was found to have the strongest associations with suicidal behaviour in this current study, as these variables have been found to have the strongest relationships with suicidal behaviours in longitudinal samples [22,23]. The plausible pathway linking drug use to suicidal behaviour is that drug users, especially adolescents addicted to marijuana suffer from depression [24][25][26] which then in uence and impair their thoughts and emotions. Drug use, in addition to smoking marijuana and alcoholism, has been observed to have the combined effects of complicating the course of depression and impairing the judgement of a person experiencing depression, and at the same time resulting in high impulsivity which leads to acute life-threatening behaviour such as suicide [25].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…It is not surprising that drug use was found to have the strongest associations with suicidal behaviour in this current study, as these variables have been found to have the strongest relationships with suicidal behaviours in longitudinal samples [22,23]. The plausible pathway linking drug use to suicidal behaviour is that drug users, especially adolescents addicted to marijuana suffer from depression [24][25][26] which then in uence and impair their thoughts and emotions. Drug use, in addition to smoking marijuana and alcoholism, has been observed to have the combined effects of complicating the course of depression and impairing the judgement of a person experiencing depression, and at the same time resulting in high impulsivity which leads to acute life-threatening behaviour such as suicide [25].…”
Section: Discussionmentioning
confidence: 72%
“…The plausible pathway linking drug use to suicidal behaviour is that drug users, especially adolescents addicted to marijuana suffer from depression [24][25][26] which then in uence and impair their thoughts and emotions. Drug use, in addition to smoking marijuana and alcoholism, has been observed to have the combined effects of complicating the course of depression and impairing the judgement of a person experiencing depression, and at the same time resulting in high impulsivity which leads to acute life-threatening behaviour such as suicide [25]. Globally, evidence suggests that those who abuse drugs are at higher risk and that is an important variable in the aetiology of suicidal behaviour [27].…”
Section: Discussionmentioning
confidence: 99%
“…The studies are often concerned with patterns and risks over time and test for social, psychological and interactional determinants of problems – e.g., within the school or family ( Olsson et al, 2019 ; Thor et al, 2019 ). Other areas of research include methodological studies ( Ledberg & Wennberg, 2014 ; Samuelsson et al, 2019 ) and intergenerational studies, focusing on how parental substance use problems translate into adverse consequences in offspring ( Hemmingsson et al, 2017 ; Landberg et al, 2019 ). A recent addition is a PhD project which uses the Stockholm Birth Cohort Multigenerational Study to examine the long-term effect of social relationships on the association between childhood disadvantage and risk of substance-related disorders in adulthood.…”
Section: Public Health From a Social Science Perspectivementioning
confidence: 99%
“…However, adverse effects of having a parent with AUD are measurable from birth and range from somatic [ 2 ] and mental disorders [ 8 ] to increased mortality [ 2 , 9 ]. Adult children of parents with AUD are at raised risk for substance use disorders [ 5 , 10 , 11 ], mental health problems [ 11 , 12 ], violence [ 2 ], and suicide [ 13 ]. Previous studies also highlight that children who grow up with a parent who has AUD are at higher risk for outcomes that can negatively affect later socioeconomic position, such as lower levels of school performance [ 14 ], unemployment during their teen years and young adulthood [ 2 ], and teenage pregnancy [ 2 ].…”
Section: Introductionmentioning
confidence: 99%